“Drink, be drunk and vomit, fall and rise no more”: Understanding the image of the cup of God’s wrath in Jeremiah 25 in light of the Mesopotamian anti-witchcraft tradition - Conti, Cristiana (Journal for the study of the Old Testament, 2024)
The apocalyptic vision of God commanding his prophet to serve the leaders of Judah the cup of his divine wrath in Jeremiah 25.15–17 and 27–28 has sparked heated theological debate. Multiple interpretations have been proposed based on intra-biblical analyses. This imagery, however, has never been compared to extra-biblical material. For example, a 7th-century BCE Assyrian incantation prayer for the patient’s social reintegration attributes his vomiting and staggering to a poisoned drink and diagnoses his curse as the result of his gods’ wrath. The depiction of the cup of God’s wrath in Jeremiah 25 may have drawn upon the Mesopotamian anti-witchcraft tradition to portray Yahweh as an exorcist who counter-curses his people. By compelling the leaders and the people of Judah to consume the same poisonous elixir, presented symbolically as the poisonous speech they had recklessly spread throughout the land, Yahweh causes his people to disgorge their internal toxicity.